May Polyphenols Have a Role Against Coronavirus Infection? An Overview of in vitro Evidence - Annunziata, Giuseppe; Sanduzzi Zamparelli, Marco; Santoro, Ciro; Ciampaglia, Roberto; Stornaiuolo, Mariano; Tenore, Gian Carlo; Sanduzzi, Alessandro; Novellino, Ettore (Frontiers in Medicine, 2020)
The coronavirus infection is constantly diffusing worldwide and the incidence of death is dramatically increasing, representing one of the greatest disasters in human history. Nowadays, no effective therapeutic approaches have been licensed, despite the rising interest of the scientific research in this specific field, and the daily growing number of publications, while the need to find novel strategies is urgent. Evidence in the literature reported the antiviral activity of polyphenols, the largest class of bioactive compounds in nature. Interestingly, a limited number of studies investigated the efficacy of polyphenols from different raw materials, directly against coronaviruses. The present manuscript aimed to report this evidence and provide a viewpoint on the possibility to use it as a start point for the development of novel natural approaches against this viral infection, eventually designing further appropriate researches.